2011
DOI: 10.1371/journal.pone.0027516
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Infants during the First 12 Months of Life: Role of Placental Malaria and Environmental Factors

Abstract: BackgroundThe association between placental malaria (PM) and first peripheral parasitaemias in early infancy was assessed in Tori Bossito, a rural area of Benin with a careful attention on transmission factors at an individual level.MethodologyStatistical analysis was performed on 550 infants followed weekly from birth to 12 months. Malaria transmission was assessed by anopheles human landing catches every 6 weeks in 36 sampling houses and season defined by rainfall. Each child was located by GPS and assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 23 publications
(33 reference statements)
4
72
2
2
Order By: Relevance
“…In parallel, epidemiological studies, including our own, have clearly documented the altered susceptibility of infants to P. falciparum infection or disease (11)(12)(13)(14)(15)(16). It has not been documented whether and how specific components of the innate immune system of such "tolerant" infants may contribute to their apparent inability to control the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel, epidemiological studies, including our own, have clearly documented the altered susceptibility of infants to P. falciparum infection or disease (11)(12)(13)(14)(15)(16). It has not been documented whether and how specific components of the innate immune system of such "tolerant" infants may contribute to their apparent inability to control the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In Benin, the study took place in the district of Come, Mono Province, located 70 km west of the economical capital, Cotonou. Malaria transmission in this area can be characterized as hyperendemic, with two peaks during the rainy seasons (April to July, September to November), and an entomological inoculation rate estimated at 35 to 60 infective bites per person per year (13). The STOPPAM study design has been described in detail elsewhere (37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital malaria rates range between 0.83 and 5.96% [17,25-29] in recent epidemiological studies. The introduction of molecular techniques has increased the detection of cord blood parasitaemia raising prevalence rates to 33% [30].…”
Section: Methods: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…A more recent study in Mozambique found that infants born to women who had clinical malaria during pregnancy, or acute placental infection, had an increased risk of clinical malaria during infancy (OR = 1.96; 95% CI, 1.13–3.41, and OR = 4.63; 95% CI 2.10–10.24, respectively) [22]. Furthermore, a cohort study conducted in Tori Bossito (Benin) confirmed the link between PM and malaria in infants through consistent entomologic and environmental follow-up [17,23]. The study findings on infants sleeping in a house with an ITN confirmed the link between PM and malaria controlled for transmission intensity, seasonality, number of anopheles, antenatal care (ANC) visits, and maternal severe anaemia (AHR = 2.13; 95% CI 1.24–3.67) compared with infants whose mothers did not have placental malaria at delivery.…”
Section: Methods: Search Strategy and Selection Criteriamentioning
confidence: 99%